PENGARUH RASIO AKTIVITAS DAN PROFITABILITAS TERHADAP HARGA SAHAM (Pada Perusahaan Farmasi di Bursa Efek Indonesia tahun 2019-2023) - Prihartanto, Andung (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2025)
This research aims to find out whether the activity and profitability ratios have an effect onstock prices. The sample for this research is pharmaceutical companies listed on the IndonesiaStock Exchange for the 2019-2023 period using a purposive sampling method, there are 5companies that meet the criteria as research samples. Hypothesis testing uses multiple linearregression analysis techniques with SPSS version 21 application tools. The research results showthat Inventory Turnover and Return on Equity do not have a significant influence on stock prices,either partially or simultaneously.